RETRACTED: Hydrodynamic Cavitation: A Novel Non-Thermal Liquid Food Processing Technology - Sun, Xun; You, Weibin; Wu, Yue; Tao, Yang; Yoon, Joon Yong; Zhang, Xinyan; Xuan, Xiaoxu (Frontiers in Nutrition, 2022)
Hydrodynamic cavitation (HC), as a novel non-thermal processing technology, has recently shown unique effects on the properties of various liquid foods. The extreme conditions of pressures at ~500 bar, local hotspots with ~5000 K, and oxidation created by HC can obtain characteristic products with high quality and special taste. Moreover, compared with other emerging non-thermal approaches, the feature of HC phenomenon and its generation mechanism determine that HC is more suitable for industrial-scale processing. This mini-review summarizes the current knowledge of the recent advances in HC-based liquid food processing. The principle of HC is briefly introduced. The effectiveness of HC on the various physical (e.g., particle size, viscosity, temperature, and stability), chemical (nutrition loss), and biological characteristics (microorganism inactivation) of various liquid foods is evaluated. Finally, several recommendations for future research on the HC technique are provided.